2011
DOI: 10.1073/pnas.1105234108
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence of quantum transport in photosynthetic light-harvesting complexes

Abstract: The photosynthetic light-harvesting apparatus moves energy from absorbed photons to the reaction center with remarkable quantum efficiency. Recently, long-lived quantum coherence has been proposed to influence efficiency and robustness of photosynthetic energy transfer in light-harvesting antennae. The quantum aspect of these dynamics has generated great interest both because of the possibility for efficient long-range energy transfer and because biology is typically considered to operate entirely in the class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
217
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 224 publications
(232 citation statements)
references
References 25 publications
(30 reference statements)
7
217
1
Order By: Relevance
“…Coherence beatings can be analyzed by performing the Fourier transform of the time traces of the peaks. A very convenient way to represent the overall complexity of oscillations in the 2D spectrum is through the Fourier maps [36][37][38][39][40][41] . They are constructed by performing the Fourier transform of the each data point in the 2D spectrum over the delay time t 2 after subtraction of slow exponential decay contributions.…”
Section: Resultsmentioning
confidence: 99%
“…Coherence beatings can be analyzed by performing the Fourier transform of the time traces of the peaks. A very convenient way to represent the overall complexity of oscillations in the 2D spectrum is through the Fourier maps [36][37][38][39][40][41] . They are constructed by performing the Fourier transform of the each data point in the 2D spectrum over the delay time t 2 after subtraction of slow exponential decay contributions.…”
Section: Resultsmentioning
confidence: 99%
“…The recent development of suitable spectroscopical techniques (see section 3) has led to the direct observation of quantum beatings on the same time scale as the one of energy transfer, and confirmed that the protein environment is key to allow the excitation to move coherently in space [18,19,123,124]. The observed coherences are surprisingly long-lived also at room temperatures, and they resist the effect of disorder [125].…”
Section: Quantum Coherence and Dissipation To The Environmentmentioning
confidence: 90%
“…These systems operate as quantum heat engines and their structure is suitable to provide an increase in the efficiency of these processes. Connections between various quantum mechanical effects, namely the coherence/ population coupling in photosynthesis [29,38], and the quantum yield enhancement in laser and solar cell quantum heat engines [27,28] were investigated. Analogy was drawn with a solar cell operation where the electron transfer efficiency may be increased by a quantum coherence between a doublet of closely lying states.…”
Section: Biological Quantum Heat Enginesmentioning
confidence: 99%